2021
DOI: 10.1186/s12989-021-00413-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-in vivo correlations of pulmonary inflammogenicity and genotoxicity of MWCNT

Abstract: Background Multi-walled carbon nanotubes (MWCNT) have received attention due to extraordinary properties, resulting in concerns for occupational health and safety. Costs and ethical concerns of animal testing drive a need for in vitro models with predictive power in respiratory toxicity. The aim of this study was to assess pro-inflammatory response (Interleukin-8 expression, IL-8) and genotoxicity (DNA strand breaks) caused by MWCNT with different physicochemical properties in different pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 64 publications
5
49
0
2
Order By: Relevance
“…Moreover, NM-401-exposed HBEC-3KT cells revealed alteration in expression of several genes involved in fibrosis and inflammation, such as tumour necrosis factor ( TNF ), interleukin 8 ( IL8 ), C-X-C motif chemokine 2 ( CXCL2 ), gelatinase ( MMP2 ), and C-C motif chemokine 3 ( CCL3 ). In agreement with our results, IL8 , which is an early pro-inflammatory biomarker, was highly expressed during nanomaterial-induced inflammation [ 10 , 25 ]. Previous studies reported that exposure to MWCNT induced persistent and chronic inflammation and fibrotic lesions in lungs, which coincide with deregulation of a number of genes associated with hallmarks of cancer [ 3 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, NM-401-exposed HBEC-3KT cells revealed alteration in expression of several genes involved in fibrosis and inflammation, such as tumour necrosis factor ( TNF ), interleukin 8 ( IL8 ), C-X-C motif chemokine 2 ( CXCL2 ), gelatinase ( MMP2 ), and C-C motif chemokine 3 ( CCL3 ). In agreement with our results, IL8 , which is an early pro-inflammatory biomarker, was highly expressed during nanomaterial-induced inflammation [ 10 , 25 ]. Previous studies reported that exposure to MWCNT induced persistent and chronic inflammation and fibrotic lesions in lungs, which coincide with deregulation of a number of genes associated with hallmarks of cancer [ 3 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our results, IL8 , which is an early pro-inflammatory biomarker, was highly expressed during nanomaterial-induced inflammation [ 10 , 25 ]. Previous studies reported that exposure to MWCNT induced persistent and chronic inflammation and fibrotic lesions in lungs, which coincide with deregulation of a number of genes associated with hallmarks of cancer [ 3 , 25 , 26 ]. However, while NM-401-exposure provided similar effects in animals and HBEC-3KT cells, no effects were observed in the mesothelial Met-5A MWCNT-exposed cells, except for an upregulation of IL8 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, it should also be noted that we have used dispersion protocols with high-energy sonication that favors stable particle suspensions, whereas the sedimentation rate of particles might be lower. Using carbon-based nanomaterials, we have observed that approximately 10% of the administered dose deposits on cells at the bottom of the cell culture wells ( 90 , 91 ). Longer incubation time increases the deposition, but it does not necessarily increase the level of DNA damage after particle exposure, which may be due to concurrent repair of DNA lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that carbon-based nanomaterials can induce chronic inflammation, interfering with endocrine functioning and xenobiotic metabolism [ 22 ], and causing fibrosis and carcinogenesis. The toxicity of carbon-based materials is mainly attributed to the generation of reactive oxygen species (ROS) triggered by carbon-based materials [ 23 ], resulting in DNA damage [ 24 ], mitochondrial dysfunction, inflammation, and apoptosis [ 25 ]. Cell damage eventually leads to different types of cell death, of which apoptosis is the primary mode and considered an important target of anti-tumor therapy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%